RIGHT TO LAND AT THE CROSSROADS: The povo de santo and the fight for dignity - Humberto Manoel de Santana Jr. (Sur: International Journal on Human Rights, 2019)
This text is a reflection on the struggle of the people of the African-derived religions in Brazil, for the right to land. The different notions of land in the dispute of civilisations and the need to include the struggle for the right to land in the agenda of the fight against religious intolerance are presented in the text. The denial of the right to land is analysed as a direct attack on the dignity of the people of African-derived religions and therefore acknowledgement of this right is, above all, acknowledgement of the dignity of these people.